Evolutionary Game Analysis of Credit Regulation for Practitioners in the Construction Industry Based on Prospect Theory - Xue, Song; Mai, Jintian; Su, Tong; Li, Na (Buildings (Basel), 2025)
Herein, an evolutionary game model involving the government and practitioners during the registration phase was constructed based on the bounded rationality assumption of prospect theory. The evolutionary stability of equilibrium points was explored under scenarios of ineffective, effective, and highly effective regulation, respectively. The construction industry is a vital pillar of the national economy, and the credit regulation of practitioners in the engineering and construction sector is an essential component of the social credit system. This model forges the foundation for maintaining a well-ordered construction market. In order to illustrate the dynamic decision-making process of working professionals in the engineering and construction fields, numerical experiments were hereby conducted to examine important factors influencing the evolutionary stable outcomes, and comparative experiments were performed by adjusting the discount factor parameter settings. The research findings include the following: (1) evolutionary trends are consistently influenced by the risk preferences of the subjects; (2) inspection intensity exerts a stronger short-term impact on low-credit groups, yet unilaterally increasing inspection intensity has limited policy effectiveness; (3) process restructuring and technological advancements significantly influence the behavior of high-credit groups but have a limited impact on low-credit groups. Additionally, this paper suggests specific regulatory strategies from three perspectives: the role of industry associations, the design of short-term disciplinary mechanisms, and the adjustment of long-term regulatory costs. These strategies are grounded on the experimental results and adapted to the distinct characteristics of high- and low-credit groups.